Suppression of Psychological Needs Among Beginning Teachers: A Self-Determination Theory Perspective on the Induction Process in Bedouin Schools - Kaplan, Haya (Frontiers in Psychology, 2021)
The study focuses on the emotional-motivational experiences of Bedouin-Arab beginning teachers during the induction period, from the perspective of Self-Determination Theory. A phenomenological study was employed. Seventy-four teachers participated, 62 of whom completed open questionnaires, while semi-structured interviews were conducted with 12 other participants. The findings indicate that the beginning teachers reported feelings of coercion, exploitation, and gender-based discrimination (autonomy suppression). They also experienced a judgmental attitude, lack of assistance, and difficulties with students (competence suppression), and their sense of relatedness to the school is impaired due to cultural factors (relatedness suppression). As a result, they expressed controlled motivation, and adopted various coping strategies. At the same time, the findings also show that when the teachers experience a sense of need satisfaction, they integrate well into the school. These findings indicate the necessity for establishing a need-supportive school environment for beginning teachers during their induction period.